The Biology of Krüppel-like Factors - Nagai, Ryozo; Friedman, Scott L.; Kasuga, Masato (Springer Japan : Imprint: Springer, 2009)
Kruppel-like factors (KLFs) are attracting great attention across a wide spectrum of biological sciences and medicine because of their remarkable biological potency and the diversity of roles they play in the physiological and pathological changes of cells and tissues. This book is a comprehensive compendium of the latest research on the molecular mechanisms of KLFs, describing their roles in transcriptional regulation, cellular differentiation and development, the pathogenesis of the liver and cardiovascular systems and cancer, and generation of ES cells and iPS cells. As the only concise treatise written to date by leading experts in the field, it serves as an authoritative review of this family of molecules and is an essential reference for all who are interested in KLFs. The book also explores the potential of KLFs as targets for novel therapeutics and diagnostics, and will be invaluable in those fields.